Rauwolfia Serpentina: Phytochemistry, Mechanisms of Action, and Clinical Implications – A Comprehensive Review - Anubhav Dubey; Vinay Kumar Patel; Vikram Kumar Sahu; Sribatsa Lanchhana Dash; Amit Mishra, (International Journal of Pharmacy Research & Technology (IJPRT), 2026)
The Indian medical system has been using the medication Rauwolfia serpentina for many generations. The medication has been referred to as Sarpgandha due to its snake-like structure. Reserpine is the main alkaloid found in Rauwolfia serpentina, despite the fact that it contains over 50 alkaloids. Even at lower dosages, reserpine is an effective antihypertensive medication. In addition to its antihypertensive and hepatoprotective properties, the stems and leaves of Rauwolfia serpentine have numerous other therapeutic applications, such as sedative, antipsychotic, antidiahoerreal, and anticancer (in breast), among others. Although the herb Rauwolfia serpentina contains the principal four Indole alkaloids, the primary goal of this context is to provide information about the primary active alkaloid Reserpine, which is more concentrated in the plant's root and plays a significant part in the plant's antihypertensive activity. Reserpine must be used at a considerably lower level in order to have an antihypertensive effect; otherwise, it may have major side effects such as sedation, lethargy, psychological depressive disorders, hypotension, nausea, bradycardia, bronchospasm, and withdrawal psychosis.